Clinical outcomes of black vs. non-black patients with locally advanced non–small cell lung cancer. (December 2017) - Vyfhuis, Melissa A.L.; Bhooshan, Neha; Molitoris, Jason; Bentzen, Søren M.; Feliciano, Josephine; Edelman, Martin; Burrows, Whitney M.; Nichols, Elizabeth M.; Suntharalingam, Mohan; Donahue, James; Nagib, Marc; Carr, Shamus R.; et al.
Highlights: Presented is the largest experience of LA-NSCLC in a predominantly black cohort. The entire cohort was treated with definitive CRT,  +/− surgical resection. Black patients were less likely to go to surgery, yet OS amid races were identical. Black and white patients have improved survival with trimodality therapy. Abstract: Objectives: The black population remains underrepresented in clinical trials despite reports suggesting greater incidence and deaths from locally advanced non-small cell lung cancer (NSCLC). We determined outcomes for black and non-black patients in a well-annotated cohort treated with either definitive chemoradiation (CRT; bimodality) or CRT followed by surgery (trimodality therapy). Materials and Methods: A retrospective analysis of 355 stage III NSCLC patients treated with curative intent at the University of Maryland, Medical Center, between January 2000-December 2013 was performed. The Kaplan–Meier approach and the Cox proportional hazards models were used to analyze overall survival (OS) and freedom-from-recurrence (FFR) in black and non-black patients. The chi-square test was used to compare categorical variables. Results: Black patients comprised 42% of the cohort and were more likely to be younger (p < 0.0001), male (p = 0.030), single (p < 0.0001), reside in lower household income zipcodes (p < 0.0001), have an Eastern Cooperative Oncology Group (ECOG) performance status >0 (p < 0.001), and less likely to undergo surgery (p < 0.0001). With a median follow-up of 15 months for all patients and 89 months for surviving patients (range:1–186 months), median OS times for black and non-black patients were 22 and 24 months, respectively (p = 0.698). FFR rates were also comparable between the two groups (p = 0.468). Surgery improved OS in both cohorts. Race was not a significant predictor for OS or FFR even when adjusted for other factors. Conclusions: We found similar oncologic outcomes in black and non-black NSCLC patients when treated with curative intent in a comprehensive cancer center setting, despite epidemiologic differences in presentation and receipt of care. Future efforts to improve outcomes in black patients could focus on addressing modifiable social disparities.